Evaluation of the antibacterial activity of CuO and ZnO nanoparticles against uropathogenic Escherichia coli - Hanan M. Abbas; Mohammed F. Al Marjani; Radhouane Gdoura (Journal of Taibah University for Science)
E. coli responsible for urinary tract infections (UTI) became resistant to obtainable therapies. So, nanotechnology appears currently as promising innovation among various strategies under development. In the present study we evaluate the antimicrobial effects of CuO and ZnO nanoparticles against E. coli isolated from UTI. Biofilm production and expression of quorum sensing genes luxS and motA were performed on E. coli treated with the nanoparticles. luxS and motA genes were detected in the tested E. coli. All isolates produced strong, moderate and weak biofilm. All isolates had a weak biofilm formation and decreased gene expression for luxS and motA genes after treatment with CuO, ZnO and their mixture. Besides, CuO and ZnO had non-toxic effects on Human Dermal Fibroblasts and neonatal normal cells. In conclusion, the mixture of CuO and ZnO had a role in decreasing the gene expression of luxS and motA genes more than each alone.